Game Edukasi Pengenalan Kebudayaan Indonesia Berbasis Android - Afan Galih Salman; Natalia Chandra; Norman Norman (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Game now is not just an entertainment but merely serves as a educational tool or the so-called educational games. We develop an educational game application on Android platform which provides information about Indonesian culture. The methodology used is the analysis method of information gathering, system design, implementation, and testing. Information about Indonesian culture is displayed in form of Android-based educational game application. Users will be expected to get a lot of information regarding the Indonesian culture.